Correlation between nosocomial pneumonia and ventilated patients in pediatric intensive care unit - Cahya Dewi; Purnomo Suryantoro; Roni Naning (Paediatrica Indonesiana, 2008)
Background NP (NP) especially YAP (ventilator-associated pneu-monia) is the most common infection in intensive care unit, whichcorrelates with the increasing of morbidity and mortality. Thereare some risk factors for development ofNP, the most importantone is duration of mechanical ventilator and reintubation.Objective To determine the correlation between NP and use ofmechanical ventilator in pediatric intensive care unit (PICU).Methods A matched case control study was conducted at Dr.Sardjito Hospital on all patients admitted to the PICU from2004 until 2006. Case group was defined as all patients who hadNP; age and sex matched control group included all patients notdiagnosed as NP. Statistical analysis was done by using chi-squareand t-tests as appropriate. Logistic regression analysis was doneto determine the role of risk factors.Results One-hundred and forty-one patients were included inthis study. The incidence of NP was 25. 7%. There was associa-tion between using mechanical ventilator (OR 1.08; 95%CI 1.07;8.20, P=0.036) and duration of using mechanical ventilator morethan four days (OR 1.75, 95%CI 1.87;18.02) with developmentof NP. There was a significant difference in event free survival ofNP between those using mechanical ventilator group and thosenot using mechanical ventilator group (P<O.OOl).Conclusion There is an association between the use of mechani-cal ventilator and duration of use of mechanical ventilator morethan four days with the development of NP